Nutrition Education Intervention to Limit Added Sugar Intake among University Female Students - Mumena, Walaa; Abdulhakeem, Fatima; Jannadi, Najwan; Almutairi, Shatha; Aloufi, Sara; Bakhishwain, Abeer; Kutbi, Hebah (Progress in Nutrition, 2020)
Background/Aim: To evaluate the effectiveness of a nutrition education intervention to limit added sugar intake among undergraduate female students. Material and Methods: This is a quasi-experimental pretest-posttest control group study that was conducted among 46 healthy participants who were selected in random (23 each in intervention and control groups). All participants were undergraduate students at Taibah University, Madinah, Saudi Arabia. The intervention included two face-to-face educational sessions and weekly messages during the 8-week study period provided information about the definition, health consequences of excessive intake, food sources, label reading, and healthy alternatives to foods containing high amounts of added sugar. Dependent variables were dietary data and anthropometrics. Independent variable was the group assignment. Results: In the intervention group, reduction of 58.3% of added sugar intake occurred, and added sugar contributed to 4.95% of the total energy. In the control group, it contributed to 10.7% of the total energy. Conclusion: The nutrition education intervention was effective in reducing over half the students’ added sugar consumption in the intervention group. The used nutrition education intervention could be adopted effectively in the community to limit added sugar intake.